Tokyo’s Kyōshō Jūtaku: Nature through the Inside, Outside and the In-Between - Klasto, Cathryn (UI Scholars Hub, 2019)
Born out of conversations with Japanese architects, as well as intimate spatial encounters with small houses (kyōshō jūtaku) in Tokyo, this paper discusses the way in which nature emerges and functions within fourth generation small housing design. Japan’s relationship with nature has generated many interconnecting architectural layers over centuries, arising out of culture, religion and the practicalities and consequences of the country’s economy, climate and experiences of natural disasters. These layers have fostered a deep and complex connection to land, and as a result, there is still a high value placed on owning one’s own plot, no matter how small. Despite how most city-based plots are often accompanied by high taxes and complicated building regulations; the lure of the land prevails. Due to domestic plot sizes rapidly reducing after the burst of the Bubble Economy in 1992, kyōshō jūtaku became a reality for those wanting to remain within the greater Tokyo area. A consequence of this reduction was that Tokyoites had less domestic contact with nature, as gardens became a luxury that most could not afford. Therefore, architects designing kyōshō jūtaku began to creatively consider new and innovative ways nature could be reclaimed and experienced through design. Through discussing examples of Tokyo’s kyōshō jūtakuin relation to inside, outside and the in-between, this paper traces how current connective and fluid manifestations of nature contribute to the destabilisation of the public-private boundary. It demonstrates how nature plays a fundamental role in building more open relationships with the city, relationships which in turn allow small houses to function as critical micro-spaces within Tokyo’s thriving urban ecology.